Archaeological excavations at the site of Jezera - Crikvina in northern Velebit (In situ, 2024)
Archaeological excavations continued at the Crikvina site in the Jezera region (northern Velebit) in September 2022. This is a continuation of archaeological trial excavations started in 2019 inside the dry stone wall building, which is known in oral tradition as the shepherd's church dedicated to St Anthony.
Keywords: Jezera-Crikvina; Velebit; church; Modern era